2019
DOI: 10.1002/rfe.1056
|View full text |Cite
|
Sign up to set email alerts
|

Empirics of currency crises: A duration analysis approach

Abstract: This paper empirically analyzes the origins of currency crises for a group of OECD economies from 1970 through 1998. We apply duration analysis to examine how the probability of a currency crisis depends on the length of non‐crisis periods, contagion channels, and macroeconomic fundamentals. Our findings confirm the negative duration dependence of a currency crisis—the likelihood of speculative attack sharply increases at the beginning of non‐crisis periods and then declines over time until it abruptly rises a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 104 publications
(148 reference statements)
0
4
1
Order By: Relevance
“…Similarly, variables for the External Sector attribute, such as Trade Openness, FDI and Current Account, were highly sensitive, indicating the significance of the behavior of a country's international trade on its currency price. This is in contrast to the findings of previous studies [1,15,41]. Similarly, the variables Total Debt and Government Spending (related to the accumulation of debt) were also highly significant, showing that high public debt ratios increase the risk of currency crises.…”
Section: Descriptive Statisticscontrasting
confidence: 99%
“…Similarly, variables for the External Sector attribute, such as Trade Openness, FDI and Current Account, were highly sensitive, indicating the significance of the behavior of a country's international trade on its currency price. This is in contrast to the findings of previous studies [1,15,41]. Similarly, the variables Total Debt and Government Spending (related to the accumulation of debt) were also highly significant, showing that high public debt ratios increase the risk of currency crises.…”
Section: Descriptive Statisticscontrasting
confidence: 99%
“…In a multi-country analysis, Komulainen and Lukkarila (2003) and Karimi and Voia (2011) found that the probability of currency crises increases with high unemployment rates, rise in inflation rates, REER, trade linkages, high public debts and trade openness. Frankel and Rose (1996) examined that the possibility of currency crises is likely to increase when the foreign direct investment to debt is low.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For their part, Reference [43] investigates the differences in a common set of indicators used in early alert systems for currency crises in the situation of Jordan and Egypt. Reference [44] empirically analyzes the causes of currency crises for a set of Organisation for Economic Co-operation and Development (OECD) countries.…”
Section: Currency Crises Predictionmentioning
confidence: 99%
“…Regarding the methods used, a considerable number of researchers have applied statistical methods to predict the currency crisis, highlighting Logit [2,12,37,38,43,45], and Probit [44,46,47]. Also, previous studies have developed computational techniques such as RNA [6,33,40,41], auto-organization map [34], support vector machine (SVM) [35], and deep neural decision trees [48].…”
Section: Currency Crises Predictionmentioning
confidence: 99%
See 1 more Smart Citation